MEMBANGUN MOTIVASI BERPRESTASI: Pengembangan Self Efficacy dan Penerapannya dalam Dunia Pendidikan - Barakatu, Abdul Rahman (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2007)
All individuals wish to get achievement in their activities done, including take formal education institution levels, but their wishes sometimes getting failure and cannot be achieved. There are a lot of students facing some difficulties and they are difficult to overcome them. One of the handicaps is psychological problem, because intrinsically he/she has failure imagination that cannot face the subject or finish his/her task. Bandura states that a construction psychology is called self efficacy. He believes that individual who has self efficacy grow up successful motivation.